Estratégias de comunicação e gestão de mídia social: análise da fan page direção do Campus São Borja – Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The purpose of the case study that will be presented to analyze the flow of information from posts, likes and comments made on the fan page of the Campus São Borja Direction - UNIPAMPA, from November 2015, in order to measure how many people access the information, we chose the case study as a research method to identify which publications had greater and lesser extent and what difference in content between them. From this it was possible to gather data and carry out a more complete analysis identifying the factors that influenced the public regarding the content posted on the page. From the analysis of the images that were selected, we can see in practice some strategies cited in the study to increase the organization's visibility and engagement of the fan page fans. We may have a somewhat clearer view of the strategies that work and that need to be improved. The goal is to use the results of this analysis to consider actions that can improve the visibility and engagement of the fans of the page campus direction São Borja.
Keywords: Mídia digital; Fan page; Sites da web; Visualização da informação; Digital media; CNPQ::CIENCIAS SOCIAIS APLICADAS